Reliability of the Indonesian version of the School-Years Screening Test for Evaluation of Mental Status-Revised as a cognitive screening tool for children - Ferriandis Harsono; Purboyo Solek; Kusnandi Rusmil (Indonesian Pediatric Society, 2016)
Background Developmental and behavioral problems are among the most common conditions of childhood. These problems affect 12−16% of children in the United States and 13−18% of children in Indonesia. Early detection of developmental deficits among children requires clinicians to screen with accurate tools. Cognitive function screening in children has been increasingly used in many clinical and educational settings. The School-Years Screening Test for Evaluation of Mental Status-Revised (SYSTEMS-R) is becoming a widely-used, reliable, and valid cognitive screening tool for children aged 4−15 years. Prior to our study, there was no Indonesian language version of the SYSTEMS-R.Objective To determine the reliability of the Indonesian translation of the SYSTEMS-R.Methods A cross-sectional study was conducted in children aged 4−15 years who understood the Indonesian language and did not have neurologic or communication impairments. Data were analysed to determine reliability (internal consistency and inter-rater reliability) of the Indonesian version of SYSTEMS-R. Internal consistency was determined using Cronbach’s alpha formula. Internal consistency is a reflection of inter-item correlation and item-to-total correlation. Inter-rater reliability was determined using the Bland-Altman method.Results This study was conducted on 133 children aged 4−15 years in a kindergarten, elementary, junior high, and senior high school in Bandung. The Indonesian version of SYSTEMS-R had significant internal consistency (Cron bach’s alpha 0.936−0.941), and the scores obtained by two raters had good agreement (difference within mean + 1.96 SD).Conclusion The Indonesian version of SYSTEMS-R is reliable for use as a cognitive screening tool for Indonesian children. [Paediatr Indones. 2016;56:149-54.].